2007
DOI: 10.1186/1475-2891-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a weight loss intervention on anthropometric measures and metabolic risk factors in pre- versus postmenopausal women

Abstract: Background: The present study examines changes in body weight, fat mass, metabolic and hormonal parameters in overweight and obese pre-and postmenopausal women who participated in a weight loss intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 29 publications
4
76
0
6
Order By: Relevance
“…There are also other studies in which the results are different from this one. The prevalence in the studies carried out in Austria (16), Germany (17), and Canada (18) was 32.6%, 36.1%, and 29.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also other studies in which the results are different from this one. The prevalence in the studies carried out in Austria (16), Germany (17), and Canada (18) was 32.6%, 36.1%, and 29.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment should include weight loss programs, regular physical exercise, and diet changes. There are studies indicating a 58% decrease in metabolic syndrome and diabetes incidence by losing 5% weight through regular exercise (31)(32)(33). Although a therapeutic lifestyle change is the first line of treatment for metabolic syndrome, it may be necessary to add antihypertensive and antilipidemic agents for the purpose of individual cardiac risk factor administration (34).…”
Section: Discussionmentioning
confidence: 99%
“…A weight loss of 5-10% of initial body weight improves metabolic profile (Ratner et al, 2005;Deibert et al, 2007;Phelan et al, 2007) and reduces the incidence of type II diabetes (Knowler et al, 2002). Furthermore, results from the Diabetes Prevention Program have shown that for every kg of weight loss, there was a 16% decrease in type II diabetes risk, emphasizing the beneficial effect of very modest weight losses (Hamman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This may happen with high prevalence of metabolic syndrome among postmenopausal women. Study of Deibert et al [42] showed that prevalence of metabolic syndrome among post-menopausal women was 36.1% and also some other studies showed that menopausal women in Canada [43], Ecuador [33] and South Korea [44] had prevalence of metabolic syndrome 31%, 41.5% and 54.6% respectively. Marjani et al showed that the prevalence of metabolic syndrome among postmenopausal women was 31% [45].…”
Section: Different Viewsmentioning
confidence: 92%
“…Studies among Korean and Chinese populations showed that prevalence of metabolic syndrome were 13.8% [44] and 17.8% for females, respectively [50]. Studies were done by Eshtiaghi [51], Ainy [52], Deilbert [42], Figueiredo Neto [53] and Heidari et al [54] have shown that prevalence of metabolic syndrome were 18.3%, 53%, 23%, 24% and 44.9%, respectively. Studies in Greece and USA have shown that prevalence of metabolic syndrome was similar in both genders [9,55].…”
Section: Different Viewsmentioning
confidence: 99%